Ownership of Medical Records in Indonesia: Discourse on Legal Certainty and Justice - Dwi Erawati, Ambar; Dini Iswandari, Hargianti (Udayana Journal of Law and Culture; Vol 6 No 2 (2022)DO - 10.24843/UJLC.2022.v06.i02.p04, 2022)
Medical disputes between patients and health workers place medical records as a vital document for evidentiary in a court proceeding. The existing law and regulations in Indonesia determine that the medical record file is owned by the health service facility, while the patient receives a summary of the medical record. This study aims to analyze medical record ownership in Indonesia from perspectives of legal certainty and justice. This article reflects normative juridical research that explores relevant primary and secondary legal materials to be analyzed deductively. This article concluded that the obligation of health workers to make medical records in proving that they have delivered properly a health service as stipulated in the law and regulations reflects a legal certainty. However, laws and regulations governing the ownership of medical records seem not to fully reflect the principle of justice since medical record files are owned by doctors, dentists, or health service facilities. Even though patients/health service recipients are entitled to requesting the files from health care facilities, the sense of justice for the patients would be in the form of easy procedures for obtaining medical records.